Evaluation of antibacterial potential of Trikatu churna and its ingredients: An in vitro study - S. B. Dahikar; S.A. Bhutada; S. K. Vibhute; V.C. Sonvale; D. H. Tambekar; S.B.Kasture (International Journal of Phytomedicine, 2010)
Herbal medicines are being used increasingly as dietary supplements to fight or prevent common disease. The dried fruits of Piper nigrum L. (Piperaceae), Piper longum L. (Piperaceae) and rhizome of Zingiber officinale Roscoe. (Zingiberaceae) were powdered and mixed together in equiproportions to get a polyherbal formulation, Trikatu churna. The aqueous, ethanol, methanol and acetone extracts of these plant’s fruits and Trikatu churna were prepared and antibacterial activities were tested by disc diffusion method against enteric bacterial pathogens such as Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, Proteus vulgaris, Staphylococcus epidermidis, Salmonella typhi, Salmonella typhimurium and Enterobacter aerogenes. The extracts of Piper longum, Piper nigrum and Zingiber officinale were found antibacterial to all bacterial pathogen tested. Trikatu churna exhibited potent antibacterial activity; this might be due to the multifunctional effect of all the three plant ingredients of Trikatu churna. Antibacterial activity of Trikatu churna and its ingredients was carried out in attempt to support the use of Trikatu churna for the treatment of enteric bacterial infections.